Matrix metalloproteinase-7 inhibitory activity of lipid extract from dwarf gulper shark (Centrophorus atromarginatus) through down-regulation of gene transcription. (March 2017) - Shiozaki, Kazuhiro; Yoshikawa, Minori; Kiguchiya, Saori; Ikeda, Asami; Kamada, Yuko; Chigwechokha, Petros Kingstone; Komatsu, Masaharu
Highlights: Lipid of dwarf gulper shark muscle attenuated MMP-7 activity in casein zymography. Shark muscle lipid decreased extracellular secretion of MMP-7 protein. Ganglioside GD1 and GM1 were suggested as active component in shark muscle. Down-regulation of mmp-7 was induced by GD1a through change of c-jun transcription. Abstract: Deep-sea living dwarf gulper shark ( Centrophorus atromarginatus ) is industrially important resource with lots of squalene in the liver, used as the resource for cosmetic ingredients, while consumption of shark muscle is limited because of ammonia smell caused by bacterial urease. Here, effect of shark muscle lipid on matrix metalloproteinase-7 (MMP-7) activity was estimated to develop the new application of shark muscle. Treatment of shark lipid toward HT-29 cells attenuated MMP-7 activity in conditioned medium accompanied with its decreased extracellular secretion. Ganglioside types in shark lipid were investigated by thin layer chromatography. Among shark gangliosides, GD1a and GM1 attenuated MMP-7 activity. GD1a negatively regulated MMP-7 polypeptide and its gene expression in HT-29 cells, whereas MAPKs signaling pathways were not altered. GD1a suppressed c-jun expression in HT-29 cells, which could negatively regulate mmp-7 transcription. This study indicated the possibility of dwarf gulper shark muscle as a material of functional food.